Hybrid Fuzzy Logic dan Profile Matching untuk Meningkatkan Klasifikasi Obat Hipertensi - Wantoro, Agus; Ariwibowo, Catur; Rahmandini, Hafizhah Harjiati (Jurnal Teknik Informatika dan Sistem Informasi, 2026)
Classification of hypertension drugs has been carried out using various methods, but the combination of Fuzzy Logic and Profile Matching (F-PM) for hypertension drug classification has not been widely reported. This study develops a new proposal with a different approach, namely combining Fuzzy Logic with the Profile Matching method. This method was evaluated using fifty clinical datasets taken from www.kaggle.com. Experimental results show that the application of Fuzzy Logic to the Profile Matching method can increase accuracy by 20.18% or 98.39%. This study also compares it with other classification methods. The results of the performance comparison show that the proposed approach is superior. This approach can be a reference for many future studies.